Partially treated palm oil mill effluent (POME) treatment by microalgae-bacteria co-culture system - Amirah binti Samsudin
Malaysia is one of the largest palm oil producers in the world. However, large amount of Palm Oil Mill Effluent (POME) is generated during the production process of the crude palm oil. Conventionally, POME is treated using biological treatment that involves both anaerobic and aerobic processes. These processes however, require long hydraulic retention time and produce methane and CO2 that can cause environmental problems. Alternatively, POME can be treated by the co-culture system of microalgae and bacteria with shorter treatment time and is environmentally friendly. In this study, two different microalgal strains (Chlorella vulgaris and Scenedesmus quadricauda) were each co-cultured with a microalgae growth-promoting bacterium (MGPB) (Azospirillum brasilense) and their effectiveness in the removal of major nutrients (ammonium and phosphorus) and chemical oxygen demand (COD) in synthetic wastewater were compared. The experiments were conducted in conical flask, continuously agitated at speed of 150 rpm. The removals were analysed by using standard method for water and wastewater examination. The results show that, the ammonium, phosphorus and COD removals were higher in C. vulgaris co-cultured system (86%, 44% and 62%, respectively) compared to that in S. quadricauda co-cultured system (48%, 31% and 52%, respectively). The most efficient co-culture system (C. vulgaris) was subsequently used to evaluate the optimum growth conditions using One Factor-at-a-Time (OFAT) and Face Centered Central Composite Design (FCCCD) under Response Surface Methodology (RSM) of the Design Expert software. The optimum growth conditions for microalgae-bacteria co-culture system obtained were 0.77 g/L for microalgae initial concentration, 104 cfu/mL for bacteria initial concentration and 1.52 day for bacteria inoculation time were applied for POME treatment and kinetics study. The co-culture system achieved 84%, 87.3% and 53.4% of ammonium, phosphorus and COD removals of the partially treated POME sample that has initial concentrations of 162 mg/L, 18 mg/L and 874 mg/L, respectively. This study shows that, co-culture system can remove higher amount of ammonium, phosphorus and COD in POME compared to axenic system under aeration growth condition. The kinetic coefficients of maximum specific growth rate (µmax) and half-saturation coefficient (ks) obtained from Lineweaver-Burk plot were 0.192 d-1 and 27.32 mg/L, respectively. The findings of this study provide an important insight into developing an efficient alternative method to treat POME that is sustainable and environmental friendly.